Belalcázar Indigenous Reserve: Law, History and Ancestral Diversity of the Territory - Araque Chacón, Andrea Carolina; Flórez Delgado, Dixon Fabián; Becerra Galvis, Zaidly Yurley (2025)
This book addresses the cultural and historical diversity and socio-cultural challenges of the indigenous reservation of Belalcázar, located in the municipality of Páez, Cauca. It examines how the interaction between indigenous, Afro- Colombian and mestizo communities has influenced the cultural identity and conservation of the ancestral territory. The main objective is to provide a comprehensive overview of the law, history, cultural diversity and contemporary issues facing the indigenous resguardo of Belalcázar. Through the analysis of its Plan de Vida and other key documents, it seeks to understand the socio cultural dynamics of the territory in order to preserve its cultural identity.The book reveals that the coexistence between indigenous, Afro-Colombian and mestizo peoples has generated considerable cultural erosion, evidenced by the decrease in the use of the ancestral language and the loss of the richness of natural resources, such as water. In addition, it describes the geographical and ecological wealth of the resguardo, taking a tour of its climate, landscapes, history and culture, and highlights how these factors shape the sociocultural identity of the region.In conclusion, the analysis presented in this book shows that, despite efforts to preserve cultural identity and territorial rights, communities continue to face significant challenges due to the influence of other cultures and external pressures. It underscores the urgent need to strengthen the protection of natural and cultural resources, as well as the importance of adopting an inclusive vision to address the resguardo’s current challenges and ensure its sustainability in the future.
Keywords: History; Ancestral territory; Traditional authority; Indigenous culture; ethnic and cultural diversity